Pengaruh Pemilihan Metode Pengakuan Pendapatan Istishna’ Terhadap Return On Asset (ROA) (Studi PT BPR Syariah Mulia Berkah Abadi Periode Tahun 2017-2019) - Kiki Rismayati; Shinta Maharani (Institut Agama Islam Negeri Ponorogo, 2022)
In selecting the revenue recognition method for the distribution of Istishna's financing, the company must consider whether the percentage of completion method or the completed contract method is necessary because the choice of revenue recognition method affects the calculation of the company's Return On Assets (ROA). This study uses primary data from PT BPR Syariah Mulia Berkah Abadi obtained from financial reports from January 2017-December 2019. The result shows that (1) Profit distribution of istishna' financing with the recognition of income by the percentage of completion method does not significantly affect Return On Assets (ROA), with a tcount of -1,373. (2) Profit on istishna' financing distribution with the recognition of income from the completed contract method does not significantly affect Return on Assets (ROA), with a tcount of -0.865. (3) From the results of the tcount of profit, the recognition of istishna' income, the completed contract method has more effect on Return On Assets (ROA).